2012
DOI: 10.5482/ha-1160
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between cancer and haemostasis

Abstract: SummaryCancer is characterized by bidirectional interrelations between tumour progression, coagulation activation, and inflammation. Tissue factor (TF), the principal initiator of the coagulation protease cascade, is centrally positioned in this complex triangular network due to its pleiotropic effects in haemostasis, angiogenesis, and haematogenous metastasis. While formation of macroscopic thrombi is the correlate of cancer-associated venous thromboembolism (VTE), a major healthcare burden in clinical haemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(11 citation statements)
references
References 99 publications
(105 reference statements)
0
10
0
1
Order By: Relevance
“…We now know that ADP induces P2Y 1 , and thromboxane A 2 stimulates TP, whereas thrombin acts through PAR1 or PAR4 [317]. In the case of thrombin activation, one of the primary initiators is tissue factor (TF), particularly in the case of tumor cells [318, 319, 317]. These platelet GPCRs, bind alpha regulatory subunits, G q alpha or G q/11 .…”
Section: Activating G Protein-coupled Receptorsmentioning
confidence: 99%
“…We now know that ADP induces P2Y 1 , and thromboxane A 2 stimulates TP, whereas thrombin acts through PAR1 or PAR4 [317]. In the case of thrombin activation, one of the primary initiators is tissue factor (TF), particularly in the case of tumor cells [318, 319, 317]. These platelet GPCRs, bind alpha regulatory subunits, G q alpha or G q/11 .…”
Section: Activating G Protein-coupled Receptorsmentioning
confidence: 99%
“…Furthermore, strong TF expression in primary tumor samples suggested that this MP TF PCA was indeed cancer cell-derived. It is therefore tempting to speculate that, in addition to TF expressed by primary tumor cells, recruitment of TF-bearing MPs into the developing thrombus contributed to the formation of tumor cell microemboli by propagating further thrombin generation and fibrin deposition following separation of the TF-rich tumor cell surface from the flowing blood [1]. However, larger studies with more practical and better standardized assays for the measurement of MP-associated TF are needed to confirm these findings.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, TF promotes hematogenous metastasis [1,3]. Specifically, coating of circulating tumor cells by fibrin(ogen)-platelet aggregates facilitates their firm adhesion to, and subsequent spreading on, the vascular endothelium and confers protection from natural killer cell-mediated cytotoxicity [4,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the association and putative role of TF in CAT is extensively investigated and reviewed17, 18, 19, 20, 21 we will only briefly summarize the most important findings. TF is the activator of the extrinsic coagulation pathway, ultimately resulting in fibrin degradation and platelet activation.…”
Section: Tissue Factormentioning
confidence: 99%